Messengers to the brain : our fantastic five senses - Martin, Paul D., 1946- (Washington, D.C. : National Geographic Society, 1984)
Describes the workings of the sense organs and explains how the brain and nerves receive and process their messages.
Includes index.
Bibliography: p. 104.
Keywords: Senses and sensation -- Juvenile literature; Sense organs -- Juvenile literature; Brain -- Juvenile literature; Senses and sensation; Sense organs; Brain